Non-noble Iron Group (Fe, Co, Ni)-Based Oxide Electrocatalysts for Aqueous Zinc–Air Batteries: Recent Progress, Challenges, and Perspectives - Yi, Jin; Liu, Xiaoyu; Liang, Pengcheng; Wu, Kai; Xu, Jie; Liu, Yuyu; Zhang, Jiujun (Organometallics, 2019)
With the increasing energy demand, energy conversion and storage technology has garnered intense attention. As one of the competitive electrochemical energy technologies, the zinc–air battery (ZAB) has been considered to be a promising candidate due to its advantages, including low cost and environmental friendliness. To overcome its technical challenges of low activity and stability of ZAB air electrode electrocatalysts, substantial efforts have been made to develop highly active and stable materials for improving the performance. In this paper, a comprehensive review of one type of the ZAB electrocatalyst, that is, iron group (Fe, Co, Ni)-based oxides, is provided. The discussion will be concentrated on the recent progress and challenges associated with this type of electrocatalyst as well as corresponding perspectives.